Civic values: Thematic studies on citizenship in Islam - Muchtarom, Moh.; Selamat, Abu Zarrin bin (Universitas Negeri Yogyakarta, 2023)
Indonesia's diverse religious, tribal, cultural, and linguistic background has resulted in frequent disputes between different groups due to the lack of firmly established civic values. As the majority population, Islamic ummah holds a vital role in establishing and managing a peaceful, fair, and prosperous society. The Qur'an, being the primary source of Islamic law, contains principles and meanings of social values that laid the foundation of the first Islamic country in Medina. Therefore, it is essential for followers of Islam to explore civic values in the Qur'an that can be integrated into Indonesian civic values. However, previous research on the concept of the ummah in the Qur'an that can construct civic values is lacking. This study aimed to address this gap by conducting qualitative research through a library research method and thematic analysis. The study identified civic values in the Qur'an that included unity, self-regulation, justice, honesty, responsibility, moderation, tolerance, rule of law, purity, change, plurality, critical thinking, and becoming a participatory, humanist, emancipatory, liberal society inseparable from the transcendental path. Integrating these values into Indonesian civic values can contribute to establishing a peaceful, fair, and prosperous society that values diversity, justice, and the rule of law.